QUANTIFICATION OF ASCORBIC ACID, BIOACTIVE COMPOUNDS AND ANTIOXIDANT ACTIVITY IN SOME UNCONVENTIONAL LEAFY GREENS (Applied Biological Research, 2023)
The present study was aimed to explore the antioxidant potential of some unconventional leafy greens, namely turnip, radish, cauliflower and carrot.  These leafy greens, procured from a local vegetable market, were analyzed  for ascorbic acid content using AOAC protocol. The standard chemical assay methods were used to ascertain the contents of bioactive compounds namely  chlorophyll, total carotenoids, flavonoids and total phenols in leaves. Anti oxidant activity was estimated based on DPPH assay. The study revealed that  ascorbic acid content in fresh leaves ranged from 62.85 to 66.27 mg 100 g-1 with highest contents in turnip and lowest in cauliflower leaves. The chloro phyll (164.5 mg 100 g-1) and total carotenoids contents (5.59 mg 100 g-1) were  significantly (p≤0.05) high in cauliflower leaves. Radish had significantly  higher flavonoid (400.6 mg QE 100 g-1) and total phenols (231.9 mg GAE 100  g-1) as compared to the other leaves. The antioxidant activity in leaves ranged  from 14.76 to 77.52% with highest value in carrot and lowest in cauliflower.  The study revealed that fresh leaves of these vegetables as a good source of  bioactive compounds may add diversity and anti-oxidants to the diets that  may protect the body from oxidative stress and free-radical damage.
Keywords: Antioxidants; carrot; cauliflower; radish; turnip; unconventional leafy greens